The effect of inquiry learning models on students' acquisition and improvement of mathematical critical thinking skills in trigonometric comparison material - Primadiana, Anneke; Priatna, Bambang Avip; Wahyudin, Wahyudin (Universitas Ahmad Dahlan, 2025)
The study aimed to analyze the effect of the inquiry learning model on students' acquisition and improvement of mathematical critical thinking skills. The method used was a quasi-experiment with a pretest-posttest control group design, involving 68 students from X State High School 1 Pagai Utara Sletan (34 students in the experimental class and 34 students in the control class). Data were collected through a mathematical critical thinking ability test on trigonometric comparison material, then analyzed using a t-test with SPSS. The results showed p = 0.006, indicating a significant difference between the effects of the inquiry-based learning model and conventional learning on students' mathematical critical thinking skills. Furthermore, the n-gain analysis showed p = 0.004, indicating that both the inquiry-based learning model and the conventional learning model influenced improvements in students' mathematical critical thinking skills. These findings demonstrate that the inquiry-based learning model is more effective in developing mathematical critical thinking. This study recommends the implementation of inquiry as an alternative learning strategy, particularly for mathematics topics requiring in-depth analysis.